Endometrial thickness in perimenopausal women with abnormal uterine bleeding - Bharatnur, Sunanda; Shetty, Trisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abnormal uterine bleeding (AUB) is the most common presenting menstrual complaint in women of perimenopausal age group. During this period, the endocrinological, biological and clinical features of approaching menopause commence. The incidence of uterine pathology increases in this age group. The objective of current study is to measure the endometrial thickness by transvaginal scan in perimenopausal patients with AUB and comparison of histopathological outcomes. Methods: This is a prospective observational study in the department of obstetrics and gynecology at Srinivas institute of medical sciences and research Centre from August 2022 to August 2023. This study included total of 115 patients with AUB between 40 to 52 years of age. Results: Among 115 patients in the study most of the patients were between 44-47 years of age. Majority of the women were multiparous (97.4 %). Transvaginal ultrasound examination revealed 105 out of 115 patients had endometrial thickness between 12-22.9mm. On HPE 92 out of 115 patients to have simple hyperplasia without atypia. Correlation between TVS and endometrial thickness shows that only 0.86% of patients with endometrial thickness between 12-22.9 has complex hyperplasia with atypia. Conclusions: Transvaginal scan is a simple, convenient and economical way to indirectly visualize the endometrial cavity. It can be used to accurately distinguish between normal and pathological endometrial conditions in patients with AUB in perimenopausal age group.